Przyjazny dla twojej kieszeni – o semantyce słowa „przyjazny” we współczesnych tekstach reklamowych - Słabczyński, Robert (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article presents semantics of an adjective friendly in contemporary advertising texts, in which it occurs not only in dictionary meanings, but also in new ones that have not been recorded in dictionaries yet. Friendly in the analysed advertisements means: ‘which is not harmful’, ‘cheap, economical’, ‘easy-to-use, simple’, ‘functional, practical, comfortable’, ‘adapted to one’s needs’, ‘meeting high standards’.